Buying and Selling Transactions of Artificial Intelligence Work that Imitate Studio Ghibli's Style Judging from Wahbah Az-Zuhaili's Opinion - azura tasya azura; Zaid Alfauza Marpaung (LP2M IAIN Palopo, 2026)
This research discusses the validity of buying and selling transactions for works of art produced by Artificial Intelligence (AI) by imitating the visual style of Studio Ghibli from the perspective of Wahbah Az-Zuhaili. The method used is a normative legal research method with a conceptual approach. The results of this research show that, according to Wahbah Az-Zuhaili, transactions of this kind are considered valid if they fulfill the conditions for buying and selling in Islam, which include clarity of the object, legal ownership, and the absence of elements of fraud and ambiguity. However, works produced by (AI) by imitating certain styles without permission may violate the principle of rights protection, so the transaction may be considered defective. Therefore, openness regarding products, compliance with rights, and implementation of a compensation system are needed to ensure that transactions comply with the principles of muamalah fiqh